2021
DOI: 10.1002/cmdc.202100131
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabelled Cyclic Bisarylmercury: High Chemical and in vivo Stability for Theranostics

Abstract: We show the synthesis of an in vivo stable mercury compound with functionality suitable for radiopharmaceuticals. The designed cyclic bisarylmercury was based on the water tolerance of organomercurials, higher bond dissociation energy of HgÀ Ph to HgÀ S, and the experimental evidence that acyclic structures suffer significant cleavage of one of the HgÀ R bonds. The bispidine motif was chosen for its in vivo stability, chemical accessibility, and functionalization properties. Radionuclide production results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Structure of A) chlormerodrin, [19][20][21] B) and C) 197m/g Hg organometallic compounds developed for radiopharmaceuticals incorporation by Gilpin et al and Pietzsch et al [25,26] D) bifunctional trithiamacrocycle reported by Blower et al [27] Chemistry-A European Journal…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Structure of A) chlormerodrin, [19][20][21] B) and C) 197m/g Hg organometallic compounds developed for radiopharmaceuticals incorporation by Gilpin et al and Pietzsch et al [25,26] D) bifunctional trithiamacrocycle reported by Blower et al [27] Chemistry-A European Journal…”
Section: Figurementioning
confidence: 99%
“…To the best of our knowledge, this is the first example of a chelator capable of yielding high radiomercury incorporation in a stable complex under biocompatible conditions (pH 7 and 37 °C), enabling the future use of a plethora of targeting vectors including temperature-sensitive biomolecules (i. e. antibodies). [25,[49][50][51] As a result, the syntheses of bifunctional NS 4 -BA and resulting bioconjugates are currently underway, with in vivo biodistribution and imaging studies planned in due course.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
See 2 more Smart Citations
“…Mercury (Hg) compounds are today mainly used in the form of organo derivates like nitromersol, thimerosal, merbromin and phenylmercuric nitrate. Organomercury are used less often in the west as disinfectants since they are considered toxic (Gilpin et al, 2021 ). Thimerosal is still used as an antiseptic in multi vaccine doses, especially in the third world countries (Geier et al, 2015 ).…”
Section: Disinfectants and Antiseptics And Their Mechanism Of Actionmentioning
confidence: 99%